Review article: the intersection of mucosal pathophysiology in HIV and inflammatory bowel disease, and its implications for therapy. Issue 10 (30th September 2014) - Ho, T. H.; Cohen, B. L.; Colombel, J.‐F.; Mehandru, S.
Summary Background The immunopathology of inflammatory bowel diseases (IBD) and HIV in the gastrointestinal (GI) tract can be viewed as ends of a spectrum with IBD being associated with 'immune excess' and HIV with 'immune paucity' within the GI tract. Aim To review the pathophysiology of IBD and HIV as they intersect in the gut immune system. Methods A search was conducted in PubMed using defined keywords 'IBD, inflammatory bowel disease, Crohn's disease, ulcerative colitis, HIV, innate immunity, mucosal layer, macrophage, cytokine, dendritic cells, adaptive immunity, CD4, T cells, Th1, Th2, natural killer T cells (NKT)'. Results Both the mucosal innate defence and adaptive immunity are profoundly affected by IBD and HIV. The pathophysiology of IBD and HIV with regard to mucosal barrier, macrophages, dendritic cells, NK cells, NKT cells and T‐cell subsets is distinct yet closely interwoven. There is limited information on the clinical manifestations of patients who have both IBD and HIV. However, recent studies suggest that the clinical course of IBD may be attenuated by concurrent HIV infection – a premise that is reasonably supported by what is known of their pathophysiology. Conclusions It is apparent that through specific pathophysiological mechanisms, HIV is capable of attenuating inflammation in IBD. In the absence of experimental models, further clinical studies are necessary to better understand patients with concurrent disease and decipher the clinical and mechanistic relationship between HIV and IBD at mucosal surfaces. Such studies are critical to guide therapeutic decisions in the management of patients with IBD infected with HIV.